การพัฒนาหลักสูตรส่งเสริมทักษะการเขียนภาษาไทย โดยใช้แนวคิดการเรียนรู้แบบประเด็นเรื่องเป็นฐาน สำหรับนักเรียนระดับชั้นมัธยมศึกษาปีที่ 2: The develop curriculum of Thai writing skills using Theme – Based Learning for Matthayom 2 students - Maneerat Keawsuk and Others, มณีรัตน์ แก้วสุก และคณะ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) สร้างหลักสูตรส่งเสริมทักษะการเขียนภาษาไทย โดยใช้แนวคิดการเรียนรู้แบบประเด็นเรื่องเป็นฐาน สำหรับระดับชั้นมัธยมศึกษาปีที่ 2 2) ศึกษาผลการใช้หลักสูตรส่งเสริมทักษะการเขียนภาษาไทย โดยใช้แนวคิดการเรียนรู้แบบประเด็นเรื่องเป็นฐาน สำหรับระดับชั้นมัธยมศึกษาปีที่ 2 กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ นักเรียนระดับชั้นมัธยมศึกษาปีที่ 2 ปีการศึกษา 2563 โรงเรียนนานาชาติยูนิตี้ คอนคอร์ด จังหวัดเชียงใหม่ จำนวน 25 คน ได้จากการสุ่มแบบง่าย (Sample Random Sampling) เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แผนการจัดกิจกรรมการเรียนรู้แบบประเด็นเรื่องเป็นฐาน 2) แบบวัดทักษะการเขียนภาษาไทย วิเคราะห์ข้อมูลโดยการหาค่าร้อยละ ค่าเฉลี่ย ( ) ส่วนเบี่ยงเบนมาตรฐาน (S.D.) และแบบทดสอบก่อนเรียน (T-test) ผลการวิจัยพบว่า 1. หลักสูตรส่งเสริมทักษะการเขียนภาษาไทย โดยใช้แนวคิดการเรียนรู้แบบประเด็นเรื่องเป็นฐาน ระดับชั้นมัธยมศึกษาปีที่ 2 โดยภาพรวมหลักสูตรมีค่าความเหมาะสมอยู่ในระดับมาก ( =4.42, S.D = 0.52) เครื่องมือที่ใช้ในการวิจัยมีค่าดัชนีความสอดคล้อง (IOC) เท่ากับ 1.00 2. ผลการใช้หลักสูตรส่งเสริมทักษะการเขียนภาษาไทย โดยใช้แนวคิดการเรียนรู้แบบประเด็นเรื่องเป็นฐาน ระดับชั้นมัธยมศึกษาปีที่ 2 พบว่า นักเรียนมีผลการประเมินทักษะการเขียนภาษาไทย หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 อีกทั้งยังมีความสามารถด้านทักษะการเขียนภาษาไทยหลังการ ใช้หลักสูตร คิดเป็นร้อยละของการพัฒนาเท่ากับ 12.53 The purposes of this research was to: 1) to develop the curriculum of Thai writing skills using theme-based method 2) to analyze the result of the implementation of Thai writing skills using theme-based for Matthayom 2 students. A group of 25 students of Matthayom 2, at Unity Concord International School, Chiangmai in the academic year of 2020 were the group chosen for implementing using the Sample Random Sampling method for this research. These group of students were chosen at random to implement both the theme-based method and the Thai writing skill method. The 2 research tools used were 1) A theme-based learning activity plan and 2) A Thai article writing test. Results of this research are analyzed using the percentage mean ( ) standard deviation method (S.D), and the T-test method. Research Findings 1.) Thai writing skills using the theme-based curriculum for Matthayom 2 students, of the secondary school level, the theme-based learning management showed the highest level of suitability ( = 4.42, S.D = 0.52). The research instrument had a conformity index (IOC) of 1.00 2.) As a result of the use of Thai writing skills using the theme-based curriculum for the Matthayom 2 students, the learning skill has a mean of a post-test score was significantly higher than the mean pre-test score (p = .05). For the students who learnt through the activity-based learning, the mean post-test score was significantly higher than the mean pre-test score of 12.53%